PENGARUH KETERAMPILAN MANAJERIAL DAN MOTIVASI KERJA KEPALA SEKOLAH TERHADAP KINERJA GURU DI SD INPRES 159 PANGI KECAMATAN RUMBIA KABUPATEN JENEPONTO - Gusniati; Sapinah (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2019)
This study aims to determine (1) description of managerial skills, principal work motivation and teacher performance in elementary school Inpres 159 Pangi District Rumbia Jeneponto District. (2) The influence of principal managerial skills on the performance of teachers of Inpres Elementary School 159 Pangi Rumbia District Jeneponto Regency. (3) The influence of principal's work motivation on teacher performance of Inpres Elementary School 159 Pangi Rumbia District Jeneponto Regency. (4) Effect of managerial skill and work motivation of principal, to teacher performance of Inpres Elementary School 159 Pangi District Rumbia Jeneponto Regency. The population in this study is all teachers of Inpres 159 Pangi elementary school amounting to 12 people and a total sample of 12 people. The method used in this research is quantitative research. The first hypothesis test, second, using simple linear regression. The third hypothesis test uses multiple linear regression. Based on the data analysis, the research results show that: (1) Description of managerial skill is high with percentage 58,3%, headmaster work motivation is high with percentage 50% and teacher performance in SD Inpres 159 Pangi is high with percentage 58,3 % (2) There is influence of principal managerial skill to teacher performance of SD Inpres 159 Pangi District of Rumbia Regency of Jeneponto. (4) There is influence of managerial skill and work motivation of headmaster, on performance of teacher of Inpres elementary school 159 Pangi District of Rumbia Regency of Jeneponto Keywords: Managerial Skills, Work Motivation, Teacher Performance.